Torture porn : popular horror after Saw - Jones, Steve (Palgrave Macmillan, 2013)
Lambasted by critics as a sign of censorial failure and even social decline, the horror subgenre known as 'torture porn' has generated a great deal of controversy during the last decade. Although torture porn films such as Saw, Hostel and The Human Centipede were highly successful and have become cultural touchstones, the term 'torture porn' remains synonymous with misogyny, obscenity and morally depravity. Arguing primarily in defense of these popular torture-themed horror films, this is the first book to offer a detailed critical examination of the 'torture porn' phenomenon, outlining the subgenre's lineage, scrutinizing responses to the sub-genre, and offering narrative analyses of the sub-genre's central box-office hits as well as the multitude of independent direct-to-DVD films that have followed in their footsteps. In doing so, this book seeks to unpick the relationships between 'porn', 'horror', 'immorality', and 'extremity'.